2006
DOI: 10.1103/physrevb.74.115329
|View full text |Cite
|
Sign up to set email alerts
|

Zero-conductance resonances and spin filtering effects in ring conductors subject to Rashba coupling

Abstract: We investigate the effect of Rashba spin-orbit coupling and of a tunnel barrier on the zero conductance resonances appearing in a one-dimensional conducting Aharonov-Bohm (AB) ring symmetrically coupled to two leads. The transmission function of the corresponding one-electron problem is derived within the scattering matrix approach and analyzed in the complex energy plane with focus on the role of the tunnel barrier strength on the zero-pole structure characteristic of transmission (anti)resonances. The liftin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
70
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 43 publications
(59 reference statements)
3
70
0
Order By: Relevance
“…12 Indeed, several groups proposed spin filters based on a single loop connected to two terminals by single-channel 1D leads. [13][14][15][16][17] If time-reversal symmetry (TRS) is conserved in such networks and the scattering matrix of the device is unitary (meaning that the number of particles scattered at a certain energy is conserved), then the 2×2 transmission and reflection matrices (in spin space) must have degenerate eigenvalues. 18,19 As a result, all directions of the spin polarization are equally probable, and there cannot be any spin filtering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Indeed, several groups proposed spin filters based on a single loop connected to two terminals by single-channel 1D leads. [13][14][15][16][17] If time-reversal symmetry (TRS) is conserved in such networks and the scattering matrix of the device is unitary (meaning that the number of particles scattered at a certain energy is conserved), then the 2×2 transmission and reflection matrices (in spin space) must have degenerate eigenvalues. 18,19 As a result, all directions of the spin polarization are equally probable, and there cannot be any spin filtering.…”
Section: Introductionmentioning
confidence: 99%
“…by adding a magnetic field. [13][14][15][16][17] Alternatively, one may increase the number of terminals connected to the device and thus generate a finite spin polarization without exploiting ferromagnetic electrodes and without applying magnetic fields. Allelectrical single-loop spin filters based on three-terminal devices have been studied before; [20][21][22][23][24] in particular, Földi et al 23 demonstrated that a symmetric-ring interferometer attached to one source and two drain terminals can act as a spin beam-splitter, which polarizes the electrons in the output leads along tunable directions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many papers proposed a single circular loop interferometer which would be sensitive to this phase and/or to its competition with the AB phase. 32,[43][44][45][46][47][48][49][50][51] The loop is connected to two leads, and the destructive interference of the waves in the two paths can sometimes block electrons with one polarization, and fully transmit electrons with the opposite polarization. Some papers also suggested to connect the loop to three leads, as in a Stern-Gerlach experiment.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In 3-lead rings, however, the condition gets relaxed. Peeters et al have shown that a 3-lead ring can act as a spin beam splitter in the presence of the RSOC.…”
Section: Introductionmentioning
confidence: 99%